Trust in E-commerce Acceptance and Use: The Case of the Philippine Online Food Delivery and Tourism Booking Services - Capistrano, Erik Paolo S. (Philippine Management Review; Vol 28 (2021), 2023)
As the Philippine business environment continues to look to information technologies for new avenues of development, growth, and sustainability, the pressure to design and develop the necessary e-commerce channels to support these trends has also increased. Therefore, given this context, academic research should also keep up to provide certain theoretically sound and empirically supported evidences to provide valuable insights. In turn, these insights should address the gaps between what the environment demands, what the industry offers, and what the customers want. This research, employing an integrated theoretical framework of trust theory and the Unified Theory of Acceptance and Use of Technology (UTAUT), attempts to contribute to this issue. Analyzing data from 399 customers of online food delivery and tourism booking services, this research identifies certain factors that affect Filipino online customers’ behavioral intentions to use technology, specifically the websites and mobile apps of these services. Through a battery of statistical analyses, this research shows that trust significantly contributes to these customers’ perceptions of their utilitarian, environmental, and hedonic expectations towards using websites and mobile apps. However, not all of these expectations exert significant influence on their behavioral intentions to use technology. This opens up theoretical and practical opportunities to enhance the strengths and address the weaknesses of these particular websites and mobile apps. Further implications and future research directions are also discussed.